Pelatihan Pembuatan Permen Jilat Sapi Sebagai Pakan Suplemen Pada Kelompok Pemuda Tani Ternak Maju Bersama Di Desa Penyaring Kecamatan Moyo Kabupaten Sumbawa - Noersidiq, Azhary; Dilaga, Syamsul Hidayat; Amin, Muhamad; Yanuarianto, Oscar; Suhubdy, Suhubdy; Dahlanuddin, Dahlanuddin; Fahrullah, Fahrullah; Maslami, Vebera (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The partner involved in community service activities is the Maju Bersama Livestock Farmer Youth Group in Desa Penyaring Kecamatan Moyo Utara Kabupaten Sumbawa. The problems faced are that farmers are very dependent on the availability of forage feed but its availability is limited during the dry season and the lack of knowledge of farmers regarding the adequacy of feed nutrition to the needs of livestock and the lack of innovation of farmers to utilize or process local feed ingredients and agricultural waste that can be made as alternative feed and feed supplements. The purpose of this activity is to help farmers to increase cattle productivity by utilizing local feed ingredients from available agricultural waste and processed in the form of supplementary feed is "Permen Jilat Sapi". The activity method includes counseling on making cow lick candy and direct training for farmers. The results of the activity were that the cow lick candy produced was classified as good with a firm texture and not soft and fragrant with the distinctive smell of molasses and corn. It was concluded that overall, the farmers' understanding of Permen Jilat Sapi after the training ranged from 80%-90%. This can be used as an indication that the activity has been successful and received a good response from farmers and as many as 75% of participants are willing to apply this feed supplement for their livestock.